Technical-tactical differences among university level taekwondo competitors by gender and weight division - Menescardi, Cristina; Bermejo, José Luis; Herrero, Carlos; Estevan, Isaac; Landeo, Raul; Falco, Coral (Revista de Artes Marciales Asiáticas, 2012)
Aim: The aim of this study was to evaluate the technical-tactical behavior of the competitors competing in the 2011 University Taekwondo Championship of Spain. Method: The sample consisted of 30 men and 31 women participating in 45 championship finals and semifinals combats. The variables analyzed were: the score, total number of actions, the type of tactical action, the height, the type of technic and kicking leg. Results/Conclusions: The Mann Whitney U test showed significant differences between men and women in total actions, circular techniques and warnings. The results also showed significant gender differences in circular actions in the flyweight and heavyweight categories, in the linear actions in bantamweight and total score in the lightweight category. Significant differences in total actions, attacking actions, actions to the trunk, performed techniques with right leg and circular techniques were also found in the middleweight division. The technical-tactical behavior of taekwondo competitors was found to differ between gender or gender and weight divisions. Women were found to perform more circular actions to the trunk with the right leg and total actions than men, who received more warnings than women.